2012
DOI: 10.1007/s13277-012-0450-z
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulation of cell motile and invasive activities by lysophosphatidic acid receptor-3 in colon cancer HCT116 cells

Abstract: Lysophosphatidic acid (LPA) mediates a wide range of biological responses with G protein-coupled transmembrane receptors (LPA receptors). So far, at least six types of LPA receptors (LPA receptor-1 (LPA(1)) to LPA(6)) have been identified. Recently, it has been reported that LPA(3) indicates opposite effects on cellular functions of cancer cells. In the present study, to assess a biological role of LPA(3) on cell migration ability of colon cancer cells, we generated LPA receptor-3 (LPAR3) knockdown (HCT-sh3-3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Our results showed that LPA 1 and LPA 3 are overexpressed in HT-29 and HCT-116 cells, which are the more invasive cell lines. It was recently shown that LPA 3 expression in HCT-116 cells inhibits LPA-induced cell migration [ 16 ], suggesting that LPA 3 is a suppressor of cell motility. Likewise, we showed in this study that LPA did not induce cell migration in HT-29 and HCT-116 cells, which express high levels of LPA 3 , whereas the increased cell migration observed in Caco-2 cells could be a result of the low levels of LPA 3 ( S1 Fig [ 10 ]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that LPA 1 and LPA 3 are overexpressed in HT-29 and HCT-116 cells, which are the more invasive cell lines. It was recently shown that LPA 3 expression in HCT-116 cells inhibits LPA-induced cell migration [ 16 ], suggesting that LPA 3 is a suppressor of cell motility. Likewise, we showed in this study that LPA did not induce cell migration in HT-29 and HCT-116 cells, which express high levels of LPA 3 , whereas the increased cell migration observed in Caco-2 cells could be a result of the low levels of LPA 3 ( S1 Fig [ 10 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it was shown that LPA 1 mediates the LPA-stimulated cell scattering of DLD-1 cells using a shRNA-lentivirus system [ 15 ]. Moreover, LPA 3 knockdown increases the migration and invasion of HCT-116 cells [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in other cells have yielded varying results. LPAR3 has been implicated in ovarian cancer progression and cell migration [45,46], but was also reported to inhibit cell migration and invasion in colon cancer cells [47]. LPAR1 has been found to induce migration in cells from breast cancer [48], pancreatic cancer [49], and hepatocellular carcinoma [50] while it inhibited metastasis and invasion in prostate organotypic models [51].…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these data mean that the ATX/LPC/LPA pathway is inhibitory for recruitment of the granulocyte in this experimental model in vivo. Although the chemoattractive effects of LPA on human neutrophil [18,19] and monocytic cell lines in vitro [20] have been reported to be positive, increasing evidence shows negative regulation of cell motility by LPA in cancerous cells that is dependent on a combination of receptor subtypes and cell types [13,[21][22][23]. The negative chemoattractive effect of the ATX/LPA pathway in regressing CL is further supported by the spatial dissociation of ATX and LPA 4 localization and by a negative correlation between increased ATX expression and decreased phagocyte number during the resolution of inflammation (stages 3 and 4).…”
Section: Discussionmentioning
confidence: 99%